2013
DOI: 10.1089/jpm.2013.0103
|View full text |Cite
|
Sign up to set email alerts
|

“To Be a Phenomenal Doctor You Have To Be the Whole Package”: Physicians' Interpersonal Behaviors during Difficult Conversations in Pediatrics

Abstract: To increase parental satisfaction and enhance the parent-physician therapeutic partnership, we recommend that physicians consider attending to the 11 interpersonal behaviors described in this manuscript, and that educational programs pay particular attention to these behaviors when training health care providers in the communication of bad news.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 20 publications
0
38
0
4
Order By: Relevance
“…In this context, it is in our view necessary to increase the trans-disciplinary level of care and services. Orioles et al [6] as well as Wigert [5] illustrate the results of a sample of 270 parents with the same requirements.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this context, it is in our view necessary to increase the trans-disciplinary level of care and services. Orioles et al [6] as well as Wigert [5] illustrate the results of a sample of 270 parents with the same requirements.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, parents' rate information provided by medical and special education practitioners as the most important sources of information, which was confirmed by research conducted by Potměšil and Pospisil [4]. Wigert et al [5] and Orioles [6] research studies focus on the communications by staff of neonatology departments and parents, and define areas of communication skills such as empathic, informative and communicative behaviours that need to be improved. The studies yielded eleven parameters that parents considered critical for acceptable communication: Empathy, availability, individual access to the child, respect for parents' knowledge about the child, leaving room for hope, body language, diligence, care above and beyond professional duty, responsibility, willingness to listen to questions, and sensitivity to the child's suffering.…”
Section: Introductionmentioning
confidence: 83%
“…3,13,[36][37][38] A metasummary of qualitative analyses of patient and family needs in pediatric palliative care found that family needs are quite high, specifically in the areas of interactions with staff, psychosocial needs, spiritual issues, decision-making, sibling needs, cultural needs, pain and symptom management, information needs, and health care delivery and accessibility. 39 More specifically, in a qualitative study of parents who had recently participated in difficult conversations with physicians in the pediatric intensive care setting, 11 specific physician interpersonal behaviors were identified as helpful to parents 40 : empathy, availability, treating the child as an individual, respecting parents' knowledge of the child, allowing hope, body contact that communicated warmth, thoroughness, going beyond the call of duty, accountability, willingness to be questioned, and attention to the suffering of the child. 40 Similarly, a study with bereaved parents found that parents value these specific elements of communication from their physicians 25 : comprehensive and complete information; clarity of information, use of clear language; ease of access to caregivers and their explanations throughout the course of care; pacing of information, soliciting of parents' emotional responses and addressing their questions; consistency of information; honesty, lack of false hope; empathy as demonstrated by verbal, nonverbal, and affective communication; summary statements and next steps.…”
Section: Improving Clinician-family Relationships and Communicationmentioning
confidence: 99%
“…Because prognosis is a major topic in assessment tools used at end of life, practitioners avoid utilizing assessment measures as a way of keeping off this sensitive topic, Orioles, et al 16 and Manalo.…”
mentioning
confidence: 99%
“…Tools which assess this parameter are therefore not used in palliative care settings locally. Orioles, et al 16 found out that clinicians are unwilling to discuss and assess sexuality as this is thought to be a less important aspect for the patient and also as a result of cultural barriers.…”
mentioning
confidence: 99%